Homogeneous Grain Boundary Passivation in Wide‐Bandgap Perovskite Films Enables Fabrication of Monolithic Perovskite/Organic Tandem Solar Cells with over 21% Efficiency - Xie, Yue‐Min; Yao, Qin; Zeng, Zixin; Xue, Qifan; Niu, Tianqi; Xia, Ruoxi; Cheng, Yuanhang; Lin, Francis; Tsang, Sai‐Wing; Jen, Alex K.‐Y.; Yip, Hin‐Lap; Cao, Yong (Advanced functional materials, 2022)
Monolithic perovskite/organic tandem solar cells have attracted increasing attention due to their potential of being highly efficient while compatible to facile solution fabrication processes. One of the limiting factors for improving the performance of perovskite/organic tandem cells is the lack of wide‐bandgap perovskites with suitable bandgap, film quality, and optoelectronic properties for front cells. In addition, the development of low‐bandgap organic bulk‐heterojunction (BHJ) rare cells with extended absorption in the infrared range is also critical for improving tandem cells. This work has carefully optimized mixed halide wide‐bandgap perovskite (MWP) films by introducing a small amount of formamidinium (FA+) cations into the basic composition of MA1.06PbI2Br(SCN)0.12, which provides an effective means to modulate the crystallization properties and phase stability of the films. At optimized conditions, the MA0.96FA0.1PbI2Br(SCN)0.12 forms high‐quality films with grain boundaries homogeneously passivated by PbI2, leading to a reduction in defect states and an enhancement in phase stability, enabling the fabrication of perovskite solar cells with a power conversion efficiency(PCE) of 17.4%. By further integrating the MWP front cell with an organic BHJ (PM6:CH1007) rare cell composed of a nonfullerene acceptor with absorption extended to 950 nm, a tandem cell with PCE over 21% is achieved. The effect of formamidinium (FA+) on modulating methylammonium (MA+) based (mixed‐halide wide‐bandgap preovskites) MWPs (MA1.06PbI2Br(SCN)0.12) crystallization properties for achieving high‐quality perovskite films is evaluated. Based on the optimized MA0.96FA0.1PbI2Br(SCN)0.12 film, a monolithic perovskite/organic tandem solar cells with a new record high‐efficiency of 21.2% is achieved.